Population pharmacokinetics and prophylactic anti‐emetic efficacy of ramosetron in surgical patients. (8th June 2016) - Lee, Yong‐Hun; Seo, Jae‐Hyeon; Min, Kyung‐Tae; Lim, Young‐Jin; Jeong, Seong‐Wook; Lee, Eun‐Kyung; Choi, Byung‐Moon; Noh, Gyu‐Jeong
Abstract : Aims: This study characterized the pharmacokinetics of ramosetron and compared prophylactic anti‐emetic efficacy with that of ondansetron in a large population. Methods: Fifty‐eight patients consented to the pharmacokinetic analysis and were assigned randomly to receive 0.3, 0.45 or 0.6 mg ramosetron after induction of anaesthesia. Blood samples were acquired at preset intervals. Non‐compartmental and population pharmacokinetic analyses were performed. In total, 1102 patients consented to the evaluation of prophylactic anti‐emetic efficacy and were allocated randomly to receive 0.3 mg ramosetron or 4 mg ondansetron at the end of surgery. An additional 16 mg ondansetron were mixed in the intravenous patient‐controlled analgesia pump of the ondansetron group. Post‐operative nausea and vomiting (PONV) were evaluated 6, 24 and 48 h post‐operatively using the Rhodes index of nausea, vomiting and retching (RINVR). Administration of rescue anti‐emetics and adverse events were evaluated. Results: The pharmacokinetic parameter estimates were V 1 (l) = 5.12, V 2 (l) = 108, CL (l⋅min −1 ) = 0.08 + (59⋅age −1 ) × 0.09, Q (l⋅min −1 ) = 1.42. The incidences of PONV in the ramosetron and ondansetron groups were 77 (13.9%) and 113 (20.6%) and 44 (7.9%) and 66 (12.0%) at 24 and 48 h post‐operatively, respectively ( P  = 0.004, 0.030). RINVR was significantly lower in the ramosetron than the ondansetron group 24 and 48 h post‐operatively ( P  = 0.003, 0.025). Use of rescue anti‐emetics and incidence of adverse events were comparable. Conclusions: A two compartment mammillary model was used to describe ramosetron pharmacokinetics. Prophylactic anti‐emetic efficacy of ramosetron was significantly better 24 and 48 h post‐operatively than that of ondansetron, particularly when the Apfel score was ≥ 3.